Emerging Implications for Extracellular Matrix-Based Technologies in Vascularized Composite Allotransplantation - Ricardo Londono; Vijay S. Gorantla; Stephen F. Badylak (Stem Cells International)
Despite recent progress in vascularized composite allotransplantation (VCA), limitations including complex, high dose immunosuppression regimens, lifelong risk of toxicity from immunosuppressants, acute and most critically chronic graft rejection, and suboptimal nerve regeneration remain particularly challenging obstacles restricting clinical progress. When properly configured, customized, and implemented, biomaterials derived from the extracellular matrix (ECM) retain bioactive molecules and immunomodulatory properties that can promote stem cell migration, proliferation and differentiation, and constructive functional tissue remodeling. The present paper reviews the emerging implications of ECM-based technologies in VCA, including local immunomodulation, tissue repair, nerve regeneration, minimally invasive graft targeted drug delivery, stem cell transplantation, and other donor graft manipulation.